Guide To Learning Basic Mathematics Easy And Fun For Children - Irmayanti; Heri irawan; MUSDALIFAH A (Kirana Publisher (KNPub), 2022)
Mathematics for some people is a subject that is not liked because they think that learning mathematics is difficult and boring. Therefore, it becomes a challenge to provide solutions and change other people's views about learning boring mathematics into fun. The method used in this service is guidance and assistance in learning mathematics which is easy and fun. Learning mathematics through the play method is one of the creative solutions in learning mathematics. Through the play method, learning mathematics will be fun and interesting. In the learning process this will greatly make children have a stronger memory than children who learn only by reading and listening. The target of this service is the children of Bungae Hamlet, Biji Nangka Village, Sinjai Borong District as many as 20 people. The results of community service with easy and fun basic mathematics tutoring activities in Bungae Hamlet, Biji Nangka Village, Sinjai Borong District, namely children who were initially only fluent in memorizing multiplications of 1 to 4 have increased to multiplication of 7 and even 9. not fluent in reciting multiplication eventually became fluent after applying the quick multiplication trick. Tutoring with quick multiplication tricks can help children improve their mathematical abilities even with limited time in the coaching process.